Analisis Efektivitas dan Efisiensi Pengelolaan APBDes di Desa Rama Indra - Dea Angelina; Ardiansyah Japlani; Karnila Ali (Jurnal Manajemen DIVERSIFIKASI, 2026)
The background to this research is the management of the Rama Indra village income and expenditure budget for the 2021-2023 period which fluctuates every year and there is a lack of openness regarding the APBDes and village information. This research aims to determine the management and effectiveness and efficiency of APBDes management in Rama Indra Village. This research uses a descriptive approach with quantitative research methods. Data collection methods used include interviews, observation and documentation. The results of the research show that the management of the village income and expenditure budget is said to be good and in accordance with Minister of Home Affairs Regulation Number 20 of 2018 concerning village financial management, while the effectiveness of the village income and expenditure budget is classified as very effective with a percentage of 90% -100% while the efficiency of The village income and expenditure budget is also classified as efficient because it is at a percentage of 90%-100%. In this research, the author suggests adding transparency to be more open to the public.